Perovskite photovoltaic device dispensed with high-boiling-point and low-boiling-point mixed anti-solvent and preparation method of perovskite photovoltaic device
By using a high and low boiling point mixed antisolvent method in the preparation process of perovskite solar cells, the crystallization process of perovskite is regulated, and the problem of antisolvents in the prior art is difficult to effectively regulate crystallization, achieving efficient photoelectric conversion and crystal quality improvement.
Patent Information
- Application Number
- CN202411771243.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-04
- Publication Date
- 2025-04-15
AI Technical Summary
In the prior art, when preparing perovskite solar cells, the physical and chemical properties and application conditions of the antisolvent are difficult to effectively regulate the crystallization process of perovskite, resulting in low crystal quality and affecting the photoelectric conversion efficiency.
The drip coating method of high and low boiling point mixed anti-solvent is used to regulate the crystallization process of perovskite and improve the crystallization quality of the film by combining the rapid extraction of low boiling point anti-solvent and the delayed crystallization characteristics of high boiling point anti-solvent.
By optimizing the crystallization process of perovskite films, the photoelectric conversion efficiency of perovskite photovoltaic cells is significantly improved, and the crystal quality and equipment performance are improved.
Smart Images

Figure CN119836191A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of perovskite solar cells, and in particular relates to a method for preparing a perovskite solar cell using a high- and low-boiling point mixed anti-solvent and a perovskite solar cell. Background Art
[0002] The anti-solvent method is currently one of the most commonly used effective methods for preparing the perovskite light-absorbing layer in perovskite photovoltaic devices. The implementation methods of the anti-solvent mainly include:
[0003] (1) Drop coating: Anti-solvent is added dropwise while spin coating the perovskite precursor solution.
[0004] (2) Steam method: enters the solution through molecular diffusion.
[0005] (3) Solvent bath method: The spin-coated film is immersed in a solvent pool of anti-solvent.
[0006] Among them, the drop coating method is the most widely studied. The main process of the drop coating method is as follows: first prepare the perovskite precursor solution and spin-coat the solution on the conductive glass / transport layer substrate, then add the anti-solvent after a few seconds and continue to spin-coat until the color of the perovskite wet film no longer changes, and finally anneal the substrate. In this process, the addition of the anti-solvent will cause the solubility of the perovskite in the mixed solvent to drop suddenly, which is conducive to the rapid precipitation of the perovskite from the solvent.
[0007] Different antisolvents have different physicochemical properties, so the antisolvents react with the perovskite precursor for different times, and their regulatory effects on the perovskite crystallization process are also different.
[0008] The physicochemical properties and application conditions of the antisolvent have an important influence on the crystallization of the perovskite light-absorbing layer. During the nucleation and growth of halide lead-based perovskite crystals, the rate of homogeneous nucleation mainly depends on the supersaturation of the perovskite precursor solution caused by the addition of the antisolvent. The higher the supersaturation, the faster the nucleation. During the growth of perovskite crystals, the complex intermediates of organic solvents and inorganic lead salts help to prolong the growth time of perovskite crystals, increase the grain size of perovskite crystals, and reduce grain boundaries, thereby improving the quality of perovskite crystals. However, overly stable solvent-solute intermediates make it difficult for the organic solvent to detach from the bottom of the crystal film after the perovskite crystals are precipitated, and leave defects and holes after annealing, reducing the quality of perovskite crystals. Therefore, optimizing the composition and application conditions of the antisolvent so that the solution system has a sufficient degree of supersaturation in the nucleation stage of perovskite crystals and delays crystallization to an appropriate degree is an effective method to improve the quality of perovskite light-absorbing layer crystals, and is also an important means to improve the comprehensive performance of perovskite photovoltaic cells. Summary of the invention
[0009] In view of the above technical problems, the purpose of the present invention is to provide a high and low boiling point mixed anti-solvent drop coating method for preparing perovskite photovoltaic devices, thereby improving the photoelectric conversion efficiency of perovskite cells by optimizing the crystallization process of perovskite films.
[0010] In order to achieve the above object, the present invention adopts the following technical solutions:
[0011] 1. A method for preparing a perovskite photovoltaic device by drop coating of a mixed anti-solvent with a high boiling point and a low boiling point, such as Figure 1 As shown, the method is processed as follows:
[0012] Step 1: preparing an electron transport layer on the surface of a substrate;
[0013] Step 2: Prepare the perovskite film on the surface of the electron transport layer by drop coating a mixed anti-solvent with different high and low boiling points;
[0014] Step 3: Deposit a hole transport layer and a back electrode on the upper surface of the perovskite film in sequence.
[0015] The step 1 specifically comprises ultrasonically cleaning the substrate in deionized water, acetone and ethanol solutions in sequence, drying with nitrogen, treating in an ultraviolet ozone cleaning machine for 10-30 minutes, and assembling the electron transport layer on the surface of the substrate by coating or evaporation.
[0016] The substrate is a conductive glass substrate. Preferably, the electron transport layer is made of metal oxides such as SnO2, TiO2, ZnO, In2O3, etc.
[0017] The step 2 specifically comprises first preparing a perovskite precursor solution, placing the substrate with the electron transport layer on a spin coater, and spin coating 50-200 μL of the perovskite precursor solution on the surface of the electron transport layer at a speed of 1000-5000 r / min for 25-60 s;
[0018] When the spin coating is carried out for 15-55 seconds, 100-300 μL of mixed anti-solvent is added at one time. After the spin coating is completed, the whole is placed on a hot stage at 100-160° C. for annealing for 10-40 minutes to obtain a perovskite film.
[0019] Preferably, the perovskite precursor solution of step 2 is a DMF and DMSO mixed solution of methylamine lead iodine MAPbI3, formamidine lead iodine FAPbI3, methylamine lead bromide MAPbBr3, formamidine lead bromide FAPbBr3, cesium lead iodine CsPbI3, cesium lead bromide CsPbBr3, methylamine tin iodine MASnI3, methylamine tin bromide MASnBr3 and their complexes. The complex is such as FACsPbI3 (a complex of FAPbI3 and CsPbI3). There is no clear ratio relationship in the mixed solution of DMF and DMSO. Generally, DMF is more than DMSO, and it is applicable as long as the perovskite precursor can be dissolved.
[0020] Preferably, the mixed anti-solvent described in step 2 includes one of the high boiling point solvents of chlorobenzene (CB) (high boiling point) or toluene (MB) (high boiling point) and one of the low boiling point solvents of dichloromethane (DCM) (low boiling point), ethyl acetate (EA) (low boiling point), diethyl ether (DE) (low boiling point), and butyl acetate (BA), thereby constituting a high and low boiling point mixed anti-solvent.
[0021] Preferably, the hole transport layer in step 3 includes but is not limited to poly 3-hexylthiophene (P3HT) and 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene (Spiro-OMeTAD).
[0022] In the step 3, a mixture of acetonitrile solutions of 4-tert-butylpyridine (tBP) and lithium bis(trifluoromethylsulfonyl)imide Li-TFSI and chlorobenzene solutions of 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene Spiro-OMeTAD is prepared, and then the mixture is spin-coated on the perovskite substrate as a hole transport layer.
[0023] In step 3, after the hole transport layer is prepared, the whole after spin coating the hole transport layer is placed in an evaporator, and a metal electrode is evaporated on the surface of the hole transport layer as a back electrode. The metal electrode is, for example, a copper film, a nickel film, an aluminum film, etc., but is not limited thereto.
[0024] 2. A perovskite photovoltaic device using a high- and low-boiling point mixed anti-solvent drop coating, prepared using the above preparation method.
[0025] The method of the present invention improves the original anti-solvent drop coating method, mixes mutually soluble high-boiling point and low-boiling point anti-solvents to prepare a mixed anti-solvent, and is used for preparing perovskite photovoltaic cells by the anti-solvent drop coating method. The method combines the advantages of low-boiling point anti-solvents that can quickly extract solvents in precursor solutions such as DMF and promote the rapid precipitation of perovskite with the characteristics of high-boiling point anti-solvents that help delay crystallization, thereby improving the crystal quality of the perovskite light-absorbing layer, and ultimately achieving the purpose of improving the photoelectric conversion efficiency of perovskite photovoltaic cells.
[0026] Compared with the prior art, the present invention has the following beneficial effects:
[0027] The present invention has found that low-boiling point anti-solvents such as dichloromethane, chlorobenzene, and ether evaporate quickly and have a short reaction time with the perovskite precursor, and can quickly extract DMF from the perovskite precursor solution to promote rapid nucleation of perovskite. High-boiling point anti-solvents such as chlorobenzene and toluene have a long reaction time with the perovskite precursor, which is beneficial to prolonging the growth time of perovskite crystals after nucleation, obtaining large-sized grains, and improving the crystallization quality of the perovskite film.
[0028] The present invention combines the characteristics of low-boiling point and high-boiling point organic solvents, prepares high- and low-boiling point mixed anti-solvents, regulates the crystallization process of perovskite, obtains high-quality perovskite films, and thus improves the conversion efficiency of perovskite photovoltaic devices. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 Schematic diagram of the preparation process of the perovskite film in the present invention.
[0030] Figure 2 It is the photoelectric conversion efficiency of the perovskite photovoltaic cells prepared in Example 1, Comparative Example 1 and Comparative Example 2 of the present invention.
[0031] Figure 3 , Figure 4 , Figure 5 The scanning electron microscope images and particle size distribution statistical result diagrams of the perovskite layers prepared in Comparative Example 1, Comparative Example 2 and Example 1 are respectively.
[0032] Figure 6 Statistical graph of the photoelectric conversion efficiency of the batteries prepared in Examples 2, 3, and 4. DETAILED DESCRIPTION
[0033] Here, exemplary embodiments are described in detail, and examples thereof are shown in the accompanying drawings. When the following description refers to the drawings, unless otherwise indicated, the same numbers in different drawings represent the same or similar elements. The implementations described in the following exemplary embodiments do not represent all implementations consistent with the present application.
[0034] The terms used in this application are for the purpose of describing specific embodiments only and are not intended to limit this application. The singular forms of "a", "said" and "the" used in this application and the appended claims are also intended to include plural forms unless the context clearly indicates other meanings. It should also be understood that the term "and / or" used herein refers to and includes any or all possible combinations of one or more associated listed items.
[0035] If the specific conditions are not specified in the embodiments of the present invention, the conditions are carried out according to conventional conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified in the reagents or instruments used, they are all conventional products that can be obtained by conventional technical means or obtained commercially. The technical scheme in the embodiments of the present invention will be clearly and completely described below in conjunction with the accompanying drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians of the art without making creative work are within the scope of protection of the present invention.
[0036] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0037] It should be noted that, in the absence of conflict, the features in the following embodiments and implementations may be combined with each other.
[0038] If no specific conditions are specified in the examples of the present invention, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. If no manufacturer is specified for the reagents or instruments used, they are all conventional products that can be obtained by conventional technical means or purchased commercially.
[0039] Embodiments of the present invention are as follows:
[0040] Example 1
[0041] The ITO glass was ultrasonically cleaned in deionized water, acetone and ethanol solution in sequence, dried with nitrogen, and treated in a UV ozone cleaning machine for 15 minutes. The SnO2 nanocolloid solution was spin-coated on the ITO glass surface and annealed on a 150°C hot stage for 1 hour to obtain a SnO2 electron transport layer. 70μL FAPbI3 was dissolved in a mixed solvent of DMF and DMSO (volume ratio of 3:1) to form a uniform solution with a concentration of 1.2mol / L. The substrate was placed on a spin coater, the spin coating speed was set to 3500r / min, the FAPbI3 solution was dried on the substrate surface for 35s, the speed was kept constant, 180μL CB / DCM (volume ratio of 1:2) was dripped into the center of the substrate, and the spin coating and drying were continued for 7s. The substrate was removed and placed on a 150°C hot stage for annealing for 15min to obtain a perovskite film. Mix 28 μL of 4-tert-butylpyridine (tBP), 17 μL of Li-TFSI in acetonitrile (concentration 250 mg / mL) and 1 mL of Spiro-OMeTAD in chlorobenzene (concentration 72.5 mg / mL), and take 60 μL to spin-coat on the perovskite substrate as a hole transport layer. Finally, place the substrate in an evaporator and evaporate 80 nm of gold film as the back electrode.
[0042] Example 2
[0043] The ITO glass was ultrasonically cleaned in deionized water, acetone and ethanol solution in sequence, dried with nitrogen, and treated in a UV ozone cleaning machine for 15 minutes. The SnO2 nanocolloid solution was spin-coated on the surface of the ITO glass and annealed on a 150°C hot stage for 1 hour to obtain a SnO2 electron transport layer. 70μL MAPbI3 was dissolved in a mixed solvent of DMF and DMSO (volume ratio of 3:1) to form a uniform solution with a concentration of 1.2mol / L. The substrate was placed on a spin coater, the spin coating speed was set to 3500r / min, the MAPbI3 solution was dried on the substrate surface for 30s, the speed was kept constant, and 200μL CB / DE (volume ratio of 1:4) was dripped into the center of the substrate. After continuing to spin dry for 5s, the substrate was removed and placed on a 100°C hot stage for annealing for 10min to obtain a perovskite film. Mix 28 μL of 4-tert-butylpyridine (tBP), 17 μL of Li-TFSI in acetonitrile (concentration 250 mg / mL) and 1 mL of Spiro-OMeTAD in chlorobenzene (concentration 72.5 mg / mL), and take 60 μL to spin-coat on the perovskite substrate as a hole transport layer. Finally, place the substrate in an evaporator and evaporate 80 nm of silver film as the back electrode.
[0044] Example 3
[0045] The ITO glass was ultrasonically cleaned in deionized water, acetone and ethanol solution in sequence, dried with nitrogen, and treated in a UV ozone cleaning machine for 15 minutes. The SnO2 nanocolloid solution was spin-coated on the surface of the ITO glass and annealed on a 150°C hot stage for 1 hour to obtain a SnO2 electron transport layer. 70μL FAPbI3 and CsPbI3 (molar ratio of 19:1) were dissolved in a mixed solvent of DMF and DMSO (volume ratio of 4:1) to form a uniform solution with a concentration of 1.0mol / L. The substrate was placed on a spin coater, the spin coating speed was set to 4000r / min, the mixed solution of FAPbI3 and CsPbI3 was dried on the substrate surface for 35s, the speed was kept constant, and 240μL CB / BA (volume ratio of 1:3) was dripped into the center of the substrate, and the substrate was removed after continuing to spin dry for 5s, and annealed on a 150°C hot stage for 10min to obtain a perovskite film. Mix 28 μL of 4-tert-butylpyridine (tBP), 17 μL of Li-TFSI in acetonitrile (concentration 250 mg / mL) and 1 mL of Spiro-OMeTAD in chlorobenzene (concentration 72.5 mg / mL), and take 60 μL to spin-coat on the perovskite substrate as a hole transport layer. Finally, place the substrate in an evaporator and evaporate 80 nm of silver film as the back electrode.
[0046] Example 4
[0047] The ITO glass was ultrasonically cleaned in deionized water, acetone and ethanol solution in sequence, dried with nitrogen, and treated in a UV ozone cleaning machine for 15 minutes. The SnO2 nanocolloid solution was spin-coated on the surface of the ITO glass and annealed on a 160°C hot stage for 1 hour to obtain a SnO2 electron transport layer. 65μL FAPbI3 and MAPbI3 (molar ratio of 9:1) were dissolved in a mixed solvent of DMF and DMSO (volume ratio of 3:1) to form a uniform solution with a concentration of 1.0 mol / L. The substrate was placed on a spin coater, the spin coating speed was set to 4000r / min, the mixed solution of FAPbI3 and MAPbI3 was dried on the substrate surface for 28s, the speed was kept constant, 280μL MB / BA (volume ratio of 1:3) was dripped into the center of the substrate, and the substrate was removed after continuing to be dried for 10s, and annealed on a 110°C hot stage for 15min to obtain a perovskite film. Mix 28 μL of 4-tert-butylpyridine (tBP), 17 μL of Li-TFSI in acetonitrile (concentration 250 mg / mL) and 1 mL of Spiro-OMeTAD in chlorobenzene (concentration 72.5 mg / mL), and take 60 μL to spin-coat on the perovskite substrate as a hole transport layer. Finally, place the substrate in an evaporator and evaporate 80 nm of gold film as the back electrode.
[0048] Example 5
[0049] The ITO glass was ultrasonically cleaned in deionized water, acetone and ethanol solution in sequence, dried with nitrogen, and treated in a UV ozone cleaning machine for 15 minutes. The SnO2 nanocolloid solution was spin-coated on the ITO glass surface and annealed on a 160°C hot stage for 1 hour to obtain a SnO2 electron transport layer. 75μL FAPbI3 was dissolved in a mixed solvent of DMF and DMSO (volume ratio of 4:1) to form a uniform solution with a concentration of 1.3mol / L. The substrate was placed on a spin coater, the spin coating speed was set to 4000r / min, and the mixed solution of FAPbI3 and MAPbI3 was dried on the substrate surface for 33s, keeping the speed unchanged, and 200μL MB / EA (volume ratio of 1:2) was dripped into the center of the substrate. After continuing to spin dry for 7s, the substrate was removed and placed on a 150°C hot stage for annealing for 10min to obtain a perovskite film. Mix 28 μL of 4-tert-butylpyridine (tBP), 17 μL of Li-TFSI in acetonitrile (concentration 250 mg / mL) and 1 mL of Spiro-OMeTAD in chlorobenzene (concentration 72.5 mg / mL), and take 70 μL to spin-coat on the perovskite substrate as a hole transport layer. Finally, place the substrate in an evaporator and evaporate an 80 nm gold film as the back electrode.
[0050] Comparative Example 1
[0051] The ITO glass was ultrasonically cleaned in deionized water, acetone and ethanol solution in sequence, dried with nitrogen, and treated in a UV ozone cleaning machine for 15 minutes. The SnO2 nanocolloid solution was spin-coated on the surface of the ITO glass and annealed on a 150°C hot stage for 1 hour to obtain a SnO2 electron transport layer. 70μL FAPbI3 was dissolved in a mixed solvent of DMF and DMSO (volume ratio of 3:1) to form a uniform solution with a concentration of 1.2mol / L. The substrate was placed on a spin coater, the spin coating speed was set to 3500r / min, the FAPbI3 solution was dried on the substrate surface for 35s, the speed was kept constant, 180μL CB was dripped into the center of the substrate, and the substrate was removed after continuing to be dried for 7s, and annealed on a 150°C hot stage for 15min to obtain a perovskite film. Mix 28 μL of 4-tert-butylpyridine (tBP), 17 μL of Li-TFSI in acetonitrile (concentration 250 mg / mL) and 1 mL of Spiro-OMeTAD in chlorobenzene (concentration 72.5 mg / mL), and take 60 μL to spin-coat on the perovskite substrate as a hole transport layer. Finally, place the substrate in an evaporator and evaporate 80 nm of gold film as the back electrode.
[0052] Comparative Example 2
[0053] The ITO glass was ultrasonically cleaned in deionized water, acetone and ethanol solution in sequence, dried with nitrogen, and treated in a UV ozone cleaning machine for 15 minutes. The SnO2 nanocolloid solution was spin-coated on the ITO glass surface and annealed on a 150°C hot stage for 1 hour to obtain a SnO2 electron transport layer. 70μL FAPbI3 was dissolved in a mixed solvent of DMF and DMSO (volume ratio of 3:1) to form a uniform solution with a concentration of 1.2mol / L. The substrate was placed on a spin coater, the spin coating speed was set to 3500r / min, the FAPbI3 solution was dried on the substrate surface for 35s, the speed was kept constant, 180μL DCM was dripped into the center of the substrate, and the substrate was removed after continuing to be dried for 7s, and placed on a 150°C hot stage for annealing for 15min to obtain a perovskite film. Mix 28 μL of 4-tert-butylpyridine (tBP), 17 μL of Li-TFSI in acetonitrile (concentration 250 mg / mL), and 1 mL of Spiro-OMeTAD in chlorobenzene (concentration 72.5 mg / mL), and spin-coat 60 μL on the perovskite substrate as a hole transport layer.
[0054] Finally, the substrate was placed in an evaporator and an 80nm gold film was evaporated as the back electrode.
[0055] The photoelectric conversion efficiency of the perovskite photovoltaic cells prepared in the above Example 1, Comparative Example 1 and Comparative Example 2 is as follows: Figure 2 As shown in the figure, it can be seen that the efficiency of the perovskite photovoltaic cell prepared in Example 1 is significantly higher than the efficiency of the perovskite photovoltaic cells prepared in Comparative Examples 1 and 2.
[0056] The scanning electron microscope images and particle size distribution statistics of the perovskite layers prepared by the methods of Comparative Example 1, Comparative Example 2 and Example 1 are shown as follows: Figure 3 , Figure 4 , Figure 5 As shown in the figure, it can be seen that the average particle sizes of the perovskite crystals are 349nm, 311nm and 380nm respectively. The perovskite crystal film prepared by the method in Example 1 has the largest grain size, the highest surface flatness and the best crystal quality.
[0057] The photoelectric conversion efficiency of the batteries prepared in Examples 2, 3 and 4 is shown in the following table: Figure 6 As shown, most of the cell efficiencies are in the range of 22%-23%, which is statistically higher than the photoelectric conversion efficiency of the cells in Comparative Examples 1 and 2.
Claims
1. A method for preparing a perovskite photovoltaic device by drop coating of a high- and low-boiling point mixed anti-solvent, characterized in that: Step 1: preparing an electron transport layer on the surface of a substrate; Step 2: Prepare the perovskite film on the surface of the electron transport layer by drop coating a mixed anti-solvent with different high and low boiling points; Step 3: Deposit a hole transport layer and a back electrode on the upper surface of the perovskite film in sequence.
2. The method for preparing a perovskite photovoltaic device by drop coating of a high- and low-boiling point mixed anti-solvent according to claim 1, characterized in that: The step 1 specifically comprises ultrasonically cleaning the substrate in deionized water, acetone and ethanol solutions in sequence, drying with nitrogen, treating in an ultraviolet ozone cleaning machine for 10-30 minutes, and assembling the electron transport layer on the surface of the substrate by coating or evaporation.
3. The method for preparing a perovskite photovoltaic device by drop coating of a high- and low-boiling point mixed anti-solvent according to claim 1, characterized in that: The substrate is a conductive glass substrate, and the electron transport layer is a metal oxide such as SnO2, TiO2, ZnO, In2O3, etc.
4. The method for preparing a perovskite photovoltaic device by drop coating of a high- and low-boiling point mixed anti-solvent according to claim 1, characterized in that: The step 2 specifically comprises first preparing a perovskite precursor solution, placing a substrate with an electron transport layer on a spin coater, and spin coating 50-200 μL of the perovskite precursor solution on the surface of the electron transport layer at a speed of 1000-5000 r / min for 25-60 s; and when the spin coating is carried out for 15-55 s, adding 100-300 μL of a mixed anti-solvent, and after the spin coating is completed, placing the whole on a hot stage at 100-160° C. for annealing for 10-40 min to obtain a perovskite film.
5. The method for preparing a perovskite photovoltaic device by drop coating of a high- and low-boiling point mixed anti-solvent according to claim 1, characterized in that: The perovskite precursor solution of step 2 is a mixed solution of methylamine lead iodine MAPbI3, formamidine lead iodine FAPbI3, methylamine lead bromide MAPbBr3, formamidine lead bromide FAPbBr3, cesium lead iodine CsPbI3, cesium lead bromide CsPbBr3, methylamine tin iodine MASnI3, methylamine tin bromide MASnBr3 and their complexes in DMF and DMSO.
6. The method for preparing a perovskite photovoltaic device by drop coating of a high- and low-boiling point mixed anti-solvent according to claim 1, characterized in that: The mixed anti-solvent described in step 2 includes a high boiling point solvent of chlorobenzene or toluene and a low boiling point solvent of dichloromethane, ethyl acetate, or ether, thereby forming a high- and low-boiling point mixed anti-solvent.
7. The method for preparing a perovskite photovoltaic device by drop coating of a high- and low-boiling point mixed anti-solvent according to claim 1, characterized in that: The hole transport layer in step 3 includes, but is not limited to, poly 3-hexylthiophene (P3HT) and 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene (Spiro-OMeTAD).
8. The method for preparing a perovskite photovoltaic device by drop coating of a high- and low-boiling point mixed anti-solvent according to claim 1, characterized in that: In the step 3, a mixture of acetonitrile solutions of 4-tert-butylpyridine (tBP) and lithium bis(trifluoromethylsulfonyl)imide Li-TFSI and chlorobenzene solutions of 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene Spiro-OMeTAD is prepared, and then the mixture is spin-coated on the perovskite substrate as a hole transport layer.
9. The method for preparing a perovskite photovoltaic device by drop coating of a high- and low-boiling point mixed anti-solvent according to claim 1, characterized in that: In the step 3, after the hole transport layer is prepared, the entire structure after spin coating the hole transport layer is placed in an evaporator, and a metal electrode is evaporated on the surface of the hole transport layer as a back electrode.
10. A perovskite photovoltaic device using high and low boiling point mixed anti-solvent drop coating, characterized in that: The invention is prepared by the preparation method 1-9 described in any one of claims 1-9.